The effects of a 6-week sand- vs. Land-based jump training programme on frontal plane knee angle and jump performance in adolescent female football players* - Richardson, M. C.; Evans, W.; Chesterton, P.; Wright, M. (Journal of Sports Sciences, 2025)
Our study investigated the effects of a six-week jump-training intervention (sand- vs land- based incorporated in a warmup), on frontal plane knee angle and jump performance of adolescent female football players. Fifty-six females were randomly allocated to either the SAND or LAND group. Thirty-nine females completed the programme twice weekly and were eligible for analysis. Two-dimensional frontal plane projection angle (FPPA), countermovement jump (CMJ) and reactive strength index (RSI) (10-5 repeated jump test) were measured 1-week pre- and post-intervention. Analysis of covariance was used to model post-intervention group differences. Compatibility curves were used to visualise parameter estimates alongside p- values, and surprisal (S) value transforms. Mean difference (X) and compatibility intervals (CI) (95|75%) for FPPA for SAND vs. LAND were X = 1.29° (-0.11 to 2.69°|0.49 to 2.10°) for the dominant limb, and X = 1.80° (0.56 to 3.04°|1.09 to 2.51°)| for the non-dominant limb. Interval estimates for jump performance were imprecise and unclear. The data indicates that including a sand surface within a jump training intervention could be beneficial when aiming to improve knee control in asymptomatic adolescent female football players, with no apparent detriment to jumping performance.